Analisa Kemampuan Literasi Numerasi dan Self-Efficacy Siswa Madrasah dalam Pembelajaran Matematika Realistik - samsul Hadi; Alpi Zaidah (Peneliti.net, 2021)
The purpose of the study was to obtain an overview of the numeracy literacy skills and self-efficacy of the tenth grade students of IPA MAN IC Lombok Timur in realistic mathematics learning (PMR). This research is a design research that develops Local Instruction Theory (LIT) in collaboration between researchers and teachers. This design consists of three phases, namely preliminary design, teaching experiment, and retrospective analysis. The research was conducted at MAN IC Lombok Timur with 24 students in class X IPA-2 consisting of 7 male students and 17 female students participating in the odd semester of the 2021/2022 academic year. Data was collected by means of tests (pre-test and post-test) of numeracy literacy and non-test (documentation studies, observations, self-efficacy questionnaires, and interviews) in analyzing students' self-efficacy levels in PMR. The results showed that students' numeracy literacy skills at PMR had increased significantly and students' self-efficacy levels were at a moderate level.